Impaired Wound Healing with Imatinib Mesylate Therapy - Ronicke, Moritz; Erfurt-Berge, Cornelia (Advances in Skin & Wound Care, 2021)
ABSTRACT: Medication-induced ulcers are generally rare. Although the tyrosine kinase inhibitor imatinib mesylate is frequently prescribed, the occurrence of ulcers related to the medication has not been previously described. Herein, the authors report a case of a patient with impaired wound healing that was attributed to imatinib mesylate treatment. Providers should maintain suspicion for medication-induced ulcers, particularly if treatment for the presumed underlying cause of an ulcer fails.
CRIS-Team Scopus Importer:2021-02-05